Gender and Lifelong Learning - Francis, Becky; Leathwood, Carole (Taylor and Francis, 2006)
This insightful book is ideal for students, researchers and policy makers wanting a sound overview of the critical issues of gender in lifelong learning. Asking pertinent questions relating to discourses on policy, the authors offer the reader a rare view of lifelong learning from a gender-focused perspective, filling a gap in the literature and moving current debate on into new areas. Questions addressed include: To what extent can the policy discourses and institutional contexts of lifelong learning be seen as masculinised and/or feminised? What are the gender implications of lifelong learning policy? In what ways are learners' identities constructed through lifelong learning? Does lifelong learning provide opportunities to challenge or transgress gender binaries? What are the implications for practice?